Relating corporate social investment with financial performance - Kobo, L.; Ngwakwe, C.C. (LLC “Consulting Publishing Company “Business Perspectives”, 2017)
Previous researchers have found conflicting results between CSI and firm financial performance. This paper moves this debate further by examining the extent to which corporate social investment (CSI) relates with corporate financial performance (CFP) from a developing country perspective. The main aim of the paper was to determine the relationship between CSI, stock price, sales turnover and return on equity (ROE) amongst the socially responsible investing (SRI) companies in the Johannesburg Stock Exchange. CSI data on the SRI companies were collected from companies’ integrated reports from 2011 to 2015. Therefore, a cross-sectional panel data arrangement was applied and the analysis was conducted using the ordinary least square (OLS). Tested at an alpha level of 0.05, the regression result produced a probability level of P < 0.01 for share price and sales turnover; and P = 10 for return on equity. Therefore, the findings revealed a strong positive and significant linkage between the SRI companies’ social investment, share price and sales turnover and no significant linkage with return on equity. These findings are consistent with previous literature findings reviewed in the paper on similar research conducted in developed countries, which showed positive and negative relationships. Findings from the literature indicate that various factors may account for conflicting results, which includes inter alia, time coverage, size of data, location, market sustainability awareness and culture. The paper contributes by revealing that whilst CSI may trigger improvement in stock price and sales turnover of SRI companies, the sales turnover might not necessarily result in boost in profit level that could engender enough return on equity within a short period time. The conflicting results from the literature is indicative of the inclusiveness in research between CSI and firm performance. Hence, the paper recommends further research to examine the relationship within a longer period of time using new sample of companies and other methods of analysis.
Journal article published in Investment Management and Financial Innovations, Volume 14, Issue 2, 2017
Keywords: Sustainable responsibility; Corporate social investment; Socially responsible investment; Stock price; Return on equity; Financial performance; Financial performance; Stock exchange; Stock price